DEVELOPING APPS WITH GPT-4 AND CHATGPT build intelligent chatbots, content generators, and more - Caelen, Olivier; Blete, Marie-Alice (O'Reilly Media, Inc., 2023)
This minibook is a comprehensive guide for Python developers who want to learn how to build applications with large language models. Authors Olivier Caelen and Marie-Alice Blete cover the main features and benefits of GPT-4 and ChatGPT and explain how they work. You'll also get a step-by-step guide for developing applications using the GPT-4 and ChatGPT Python library, including text generation, Q&A, and content summarization tools. Written in clear and concise language, Developing Apps with GPT-4 and ChatGPT includes easy-to-follow examples to help you understand and apply the concepts to your projects. Python code examples are available in a GitHub repository, and the book includes a glossary of key terms. Ready to harness the power of large language models in your applications? This book is a must. You'll learn: The fundamentals and benefits of ChatGPT and GPT-4 and how they work How to integrate these models into Python-based applications for NLP tasks How to develop applications using GPT-4 or ChatGPT APIs in Python for text generation, question answering, and content summarization, among other tasks Advanced GPT topics including prompt engineering, fine-tuning models for specific tasks, plug-ins, LangChain, and more.